Soldiering and the the Rites of Passage (Global Journal of Human-Social Science, 2016)
Armed forces are kept by the states for purposes of defense Despite various claims armies never become redundant The need for protection of the boundaries even though a seemingly old-fashioned idea is always there as a sheer reality to reckon with for any given country Being exposed to aggression is a sad probability which may occur suddenly and hit the fate of any nation A lot of philosophical sentences about the lacking of human reasoning in soldierly ways have also been uttered Now a soldier differs from a civilian and the transformation of the latter being into the former one is a radical social metamorphosis including moral and physical factors From an anthropological viewpoint it is a full initiation ritual or passage rite This fact alone renders all martial activities entirely rational and compatible with logic